2015
DOI: 10.1038/srep17668
|View full text |Cite
|
Sign up to set email alerts
|

β-sitosterol interacts with pneumolysin to prevent Streptococcus pneumoniae infection

Abstract: Pneumolysin is one of the major virulence factors elaborated by Streptococcus pneumoniae; this toxin is a member of the cholesterol-dependent cytolysins. Engagement of cholesterol induces the formation of a multi-subunit complex by pneumolysin that lyses host cells by forming pores on the membrane. Because pneumolysin released by bacteria which have been killed by conventional antibiotics is still active, agents capable of directly attacking the toxin are considered advantageous against antimicrobials in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 31 publications
(41 reference statements)
1
55
0
Order By: Relevance
“…In spite of a recent study indicate that rumen microorganisms may degrade several cyanotoxins [33], the threat from cyanotoxins cannot be ignored. Our results revealed that BSS might inhibit the growth of cyanobacteria, since its antibacterial activity has been documented [34,35].…”
Section: Discussionmentioning
confidence: 53%
“…In spite of a recent study indicate that rumen microorganisms may degrade several cyanotoxins [33], the threat from cyanotoxins cannot be ignored. Our results revealed that BSS might inhibit the growth of cyanobacteria, since its antibacterial activity has been documented [34,35].…”
Section: Discussionmentioning
confidence: 53%
“…EGCG can bind to the cleft between domains three and four in PLY via hydrogen bonding and hydrophobic interactions. This cleft is reported to participate in reactivity and is important for PLY . In detail, the binding model of EGCG with PLY revealed that the side chain of EGCG can form strong interactions with Ser256, Glu277, Tyr358 and Arg359, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…103 Also included in this category are βsitosterol, a plant-derived cholesterol mimic, as well as liposomes composed of sphingomyelin/cholesterol. [104][105][106] Several other plant-derived agents, viz.…”
Section: Inhibitors Of the Cytolytic Activity Of Pneumolysinmentioning
confidence: 99%